EDUCATION: THE KEY TO PERSONAL AND SOCIETAL DEVELOPMENT - Abdullayeva Ozoda (TALABALAR ILMIY KONFERENSIYASI "TILSHUNOSLIK MASALALARI – YOSH TADQIQOTCHILAR NIGOHIDA", 2025)
Education is often regarded as the backbone of society, and rightly so. It is the foundation upon which individuals build their futures and communities construct sustainable growth. In this article, we will explore the multifaceted role of education, the challenges it faces in the modern world, and the measures necessary to ensure its effectiveness and accessibility.